P33 The impact of certain underlying clinical conditions on the risk of developing hospitalised pneumonia in england. (December 2018) - Campling, JA; Jones, D; Chalmers, JD; Vyse, A; Madhava, H; Slack, M
Abstract : Introduction/background: Specific risk groups are at increased risk of hospitalisation and death from non-invasive pneumococcal disease. Evidence showing the increased odds ratio in these risk groups for developing hospitalised pneumonia in England is missing. Aim: To quantify the odds of developing hospitalised pneumonia for 6 key risk groups as defined by The Green Book (UK vaccination policy guide) compared to 'healthy controls', with no risk group diagnosis, using the Hospital Episodes Statistics (HES) database. Materials and methods: We retrospectively analysed the Hospital Episodes Statistics database, which includes analysed data on the entire ≥18 years population of England for episodes of hospitalised pneumonia over a period of 3 years. Patients and controls were identified by ICD-10 codes. Healthy controls were in-patient admissions for tooth extraction. Odds ratios were calculated while simultaneously adjusting for gender, age, Charlson Comorbidity Index, ethnicity, geography and deprivation. Results: Odds ratio of developing hospitalised pneumonia for specific risk groups compared to healthy controls. Conclusion: This is the first study of an entire adult population quantifying the increased odds of hospitalised pneumonia among patients with these underlying risk factors. These individuals are at a significant increased risk of developing hospitalised pneumonia and that the odds are substantially higher for those with CRD, CLD and BMT. These data support the potential benefit of adopting a targeted prevention strategy among specific risk groups.